Modeling of acid dye decolorization by TiO2–Ag2O nano-photocatalytic process using response surface methodology - M.E. Olya; M. Vafaee; M. Jahangiri (Journal of Saudi Chemical Society)
In the present study, TiO2–Ag2O nanophotocatalyst was synthesized and characterized by the sol–gel method. Dye removal ability of the surface modified with TiO2–Ag2O nanophotocatalyst by a photocatalytic reactor was investigated. The physical characteristics of TiO2–Ag2O were studied by energy-dispersive X-ray spectroscopy, scanning electron microscopy and X-ray diffraction. Acid red 18 (Ponceau 4R) was used as a model compound. The effect of operational parameters ((H2O2/dye), catalytic amount and pH) on dye removal was evaluated. Response surface methodology was used for the analysis of the dye removal data. The experimental checking in these optimal conditions confirmed good agreement with RSM results. Development of strategies for modeling and optimization led to fast and successful commercialization of photocatalytic processes. Response surface methodology in combination was used for modeling and optimization of Ponceau 4R (AR18) degradation in a batch photoreactor. Results of the study indicate a perfect and optimized model for the high ability of the newly synthesized photocatalyst in optimum conditions. Keywords: RSM, Experimental design, TiO2–Ag2O nanophotocatalyst, Dye removal